Financial Inclusion Scheme and Poverty Alleviation in Nigeria (2004 – 2019): Array - Aribaba, F. O.; Adedokun, Olusegun J.; Oladele, Rotimi; Babatunde, A. D.; Ahmodu, Olamide A.; Olasehinde, Sunday A. (Acta Universitatis Danubius. Œconomica, 2020)
The study explores the effect of the financial inclusion scheme on poverty alleviation among the low-income earners in Nigerian between the periods of (2004 – 2019). The study employed a causal-comparative research design. Annual data was gathered from the Apex Bank in Nigeria (CBN) through the World Bank Indicators statistical bulletin 2019 online edition. The statistical methods used are ordinary least squares (OLS) and error correction model (ECM). The Augmented Dickey-Fuller (ADF) tests were piloted to investigate the stationary properties through time-series test. The null hypothesis was tested at 5% level of significance. The independent variables are; Loan to Depositor Ratio (LDR), Loan to Rural Areas (LRA) such as local farmers, Financial Deeping Indicators (FDI) and Social Investment Loan (SIL) to SMEs while dependent variables are Poverty Index (PI) and Per Capita Income (PCI) respectively. The study shows that financial inclusion schemes play a significant effect on poverty alleviation among the low-income earners in Nigerian. It also reduces poverty level and increases per capita income thereby enhance the standard of living through the new social investment scheme. The study recommended that the apex bank should review their policies to suit the needs of the low-income earners and subsidize the interest rates to facilitate easy accessibility of financial services of her citizenry, increase income generation and promote economic growth thereby reduce poverty level and enhance the citizen standard of living.